Endowing Teachers: The Insightful Effects of Soft Skills on Work Performance of Primary School Teachers - Sahar, Shaista; Ullah, Naeem; Hussain, Mazhar (Annals of Human and Social Sciences, 2024)
The current study is designed to explore the effect of soft skills on work performance of primary school teachers. Soft skills are inevitable for the success of any individual and professional. Primary school teachers are the foundation makers of any nation and have a great responsibility to imprint their students. The study was descriptive, a cluster random sampling technique was employed and data was collected from primary school teachers working in 245 schools which were selected as sample clusters for the study. A total of 930 questionnaires were distributed of which 840 responded. Descriptive and inferential statistical analysis was done. Study results showed that soft skills have a significant effect on and positive correlation with the work performance of teachers. Soft skills mastery guarantees well-rounded and adjustable teachers, proficient in interpersonal dynamics and professional settings so it is recommended that initiatives must be taken to develop soft skills in teachers.